Morphometric Analysis of Craniodental Characters of the House Rat, Rattus rattus (Rodentia: Muridae) in Peninsular Malaysia - Mohamad Ikbal, Nurul Huda; Pathmanathan, Dharini; Bhassu, Subha; Simarani, Khanom; Omar, Hasmahzaiti (Penerbit Universiti Kebangsaan Malaysia, 2019)
Rattus rattus which is believed to be native to India is easily found in all continents of the world. With the absence of R. rattus from lineage I and the presence of lineage IV in Southeast Asia, little is known about how rodent morphology varies biogeographically. We evaluate the skull morphometrics in the population of R. rattus in Peninsular Malaysia and examine the intraspecific variation of the skull by assessing 20 craniodental characters of 130 R. rattus specimens. After observing the correlation matrix, highly correlated characters were removed and the remaining 14 craniodental characters were analysed using the conventional morphometrics method via univariate and multivariate statistics. We assessed the impact of age, sex and geographical factors (latitude, longitude and precipitation) on craniodental size. Male and female specimens were analysed separately since statistically significant sexual dimorphism was present. Males showed greater craniodental measurements compared to females. Three distinct age groups (C2, C3 and C4) were visible in the principal component analysis (PCA) and canonical variate analysis (CVA) plots for male and female specimens. Ages C2 and C3 shared similarities in craniodental measurements while C4 showed variability compared to C2 and C3. None of the geographical factors studied showed statistical significance for both male and female R. rattus. The results obtained from this study could potentially be a yardstick to observe if similar variations in craniodental traits are present in R. rattus from other countries in the Southeast Asian region. © 2019 Penerbit Universiti Kebangsaan Malaysia. All rights reserved.